Cushing's disease in childhood: presentation, investigation, treatment and long-term outcome. - Savage, M; Lienhardt, A; Lebrethon, M; Johnston, L; Huebner, A; Grossman, AB; Afshar, F; Plowman, P; Besser, G (2001)
Seventeen patients with Cushing's disease (CD) were treated from 1978 to 2000. There were 11 males and 6 females aged 6.8-18.8 years (mean age 13.0 +/- 5.9 years). Presenting features were: weight gain (100%); growth failure (71%); hirsutism (53%); striae (53%); hypertension (47%). Mean age of patients with striae was 15.2 +/- 2.3 years, without striae 10.3 +/- 3.3 years. Median height SDS was -1.81 (range -0.28 to -4.17), 53% having height SDS < -1.8. The height velocity in 6 subjects was subnormal (0.9-3.8 cm/year). Median BMI SDS was 2.29 (range 1.72-5.06). Cushing's disease was confirmed by detectable serum ACTH, median 28 ng/l (range 12-99, NR <10-50) (n = 15); loss of cortisol circadian rhythm values at midnight ranging from 216 to 1,080 nmol/l (NR <50) (n = 15); lack of cortisol suppression (NV < 50 nmol/l) during low-dose dexamethasone suppression test (LDDST) (0.5 mg 6-hourly x 8) (n = 14); and >50% suppression of cortisol compared with the basal value during high-dose dexamethasone suppression test (HDDST) (2 mg 6-hourly x 8) (n = 14). A CRH test (1 microg/kg i.v.) showed an increase of cortisol from 12 to 217% (median 73.5%) (n = 16). Pituitary imaging (CT/MRI) showed an image consistent with microadenoma in 6/17 patients, but there was concordance between pituitary imaging and surgical findings in 1/11 patients (9%). Inferior petrosal sinus sampling (IPSS) for ACTH after CRH was performed in 11 subjects (age 10.7-18.8 years). Central to peripheral ACTH ratios were >2 (2.5-157.2) in 10/11 patients. The inter-petrosal sinus ACTH gradient was >1.4 in 10 patients (2.1-20.8), indicating lateralization of ACTH secretion. In 10 patients (91%), the side of the tumour on IPSS was predictive of findings at surgery. Therapy consisted of transsphenoidal microadenomectomy (TSS) in 16 patients and bilateral adrenalectomy (1978) in 1. Following TSS alone, 7 patients were cured (cortisol <50 nmol/l) and 2 were in remission (cortisol <300 nmol/l), i.e. 56%. Seven had persisting hypercortisolaemia and underwent pituitary irradiation (4,500 cGy). Therapeutic outcome for a median of 8 years (0.5-24 years) resulted in cure of CD in 14/17 patients (82%) and remission in 1. Linear growth after TSS +/- pituitary irradiation in 10 subjects showed no short-term catch-up growth, with peak growth hormone (GH) 0.5-20.9 mU/l to insulin tolerance test (ITT)/glucagon. Eight patients were treated with human growth hormone (hGH) (14 U/m(2)/week) combined in 3 with GnRH analogue. The mean final (n = 6) or latest (n = 4) height SDS was -1.36. The difference between final/latest height SDS and target height SDS was 0.93 +/- 1.13, i.e. less (p = 0.005) than the difference between height SDS and target height SDS at presentation, i.e. 1.72 +/- 1.26, indicating long-term catch-up growth.